REVISED LOAD BALANCING ALGORITHM IN CLOUD COMPUTING (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cloud computing is one of the latest and upcoming paradigm that offers huge benefits such as reduced time to market, unlimited computing power and flexible computing capabilities. It is a model that provides an on-demand network access to a shared pool of computing resources It comprises a large number of concepts primarily Load Balancing, Scheduling, etc. This paper discusses load balancing as a mechanism to distribute the workload evenly to all nodes in the system to achieve a higher resource utilization and user satisfaction. It helps in allocation and de-allocation of instances of applications withoutÂ  Â failure. This paper reports a new load balancing technique and its comparison with existing algorithm providing better results.Â